Loss of melusin is a novel, neuronal NO synthase/FoxO3‐independent master switch of unloading‐induced muscle atrophy - Maurizio Vitadello; Matteo Sorge; Elena Percivalle; Elena Germinario; Daniela Danieli‐Betto; Emilia Turco; Guido Tarone; Mara Brancaccio; Luisa Gorza (Wiley, 2020)
Abstract Background Unloading/disuse induces skeletal muscle atrophy in bedridden patients and aged people, who cannot prevent it by means of exercise. Because interventions against known atrophy initiators, such as oxidative stress and neuronal NO synthase (nNOS) redistribution, are only partially effective, we investigated the involvement of melusin, a muscle‐specific integrin‐associated protein and a recognized regulator of protein kinases and mechanotransduction in cardiomyocytes. Methods Muscle atrophy was induced in the rat soleus by tail suspension and in the human vastus lateralis by bed rest. Melusin expression was investigated at the protein and transcript level and after treatment of tail‐suspended rats with atrophy initiator inhibitors. Myofiber size, sarcolemmal nNOS activity, FoxO3 myonuclear localization, and myofiber carbonylation of the unloaded rat soleus were studied after in vivo melusin replacement by cDNA electroporation, and muscle force, myofiber size, and atrogene expression after adeno‐associated virus infection. In vivo interference of exogenous melusin with dominant‐negative kinases and other atrophy attenuators (Grp94 cDNA; 7‐nitroindazole) on size of unloaded rat myofibers was also explored. Results Unloading/disuse reduced muscle melusin protein levels to about 50%, already after 6 h in the tail‐suspended rat (P < 0.001), and to about 35% after 8 day bed rest in humans (P < 0.05). In the unloaded rat, melusin loss occurred despite of the maintenance of β1D integrin levels and was not abolished by treatments inhibiting mitochondrial oxidative stress, or nNOS activity and redistribution. Expression of exogenous melusin by cDNA transfection attenuated atrophy of 7 day unloaded rat myofibers (−31%), compared with controls (−48%, P = 0.001), without hampering the decrease in sarcolemmal nNOS activity and the increase in myonuclear FoxO3 and carbonylated myofibers. Infection with melusin‐expressing adeno‐associated virus ameliorated contractile properties of 7 day unloaded muscles (P ≤ 0.05) and relieved myofiber atrophy (−33%) by reducing Atrogin‐1 and MurF‐1 transcripts (P ≤ 0.002), despite of a two‐fold increase in FoxO3 protein levels (P = 0.03). Atrophy attenuation by exogenous melusin did not result from rescue of Akt, ERK, or focal adhesion kinase activity, because it persisted after co‐transfection with dominant‐negative kinase forms (P < 0.01). Conversely, melusin cDNA transfection, combined with 7‐nitroindazole treatment or with cDNA transfection of the nNOS‐interacting chaperone Grp94, abolished 7 day unloaded myofiber atrophy. Conclusions Disuse/unloading‐induced loss of melusin is an early event in muscle atrophy which occurs independently from mitochondrial oxidative stress, nNOS redistribution, and FoxO3 activation. Only preservation of melusin levels and sarcolemmal nNOS localization fully prevented muscle mass loss, demonstrating that both of them act as independent, but complementary, master switches of muscle disuse atrophy.